An Updated Review of Pharmacological Properties on Citrus Limetta (Mosambi). - Ushnik Das; Mainak Chakraborty; Nilanjan Sarkar (International Journal of Pharma and Bio Sciences, 2021)
Citrus fruit has great importance all around the world. Many citrus species are cultivated in Asian subcontinent. Among them, Sweet lime (Citrus limetta) also known as “mosambi”are harvested in the Indian subcontinent. Herbal drugs are considered to be the oldest remedy for any disease. Use of herbal medicines dates back to 5000 years. An herbal drug has grown exponentially in recent years all across the world. India is considered as the birthplace for Ayurveda, Yoga, Unani, Siddha, Homeopathy and Naturopathy. Because of the belief that”everything can be a drug”, physicians started collection of herbs and popularized it. It has many pharmacological effects and its constituents are extensively used in many clinical applications. This review aimed to explore the constituents present in Citrus limetta and their medicinal uses in different diseases which provide approval for further pharmacological and clinical investigations. This review gives a bird’s eye view mainly on the biological activity its preventive medicinal uses and applications on inflammation, bacterial, viral, diabetes, hyperlipidemia, anxiety, Alzheimer, urinary disorders and for improvement of immune systems. According to the World Health Organization, 75% of the world population use herbal therapies as their primary treatment. It is more popular in rural areas of developing countries. The reason for attaining widespread acceptability includes antimalarial, anti-diabetic, antioxidant, neotropic, lipid lowering activity and minimal side effects with greater efficacy. It is a rich source of Vitamin C and has phytoconstituents like flavonoids, carotenoids, and terpenes. Among them D- limonene is the most abundant constituent. Objective of the review is to maximize the review of Citrus limetta focusing the effect over different ailments and isolation of different constituents from this plant for different sets of diseases.